Native peoples of the world an encyclopedia of groups, cultures, and contemporary issues - Danver, Steven (Sharpe Reference, 2013)
This work examines the world's indigenous peoples, their cultures, the countries in which they reside, and the issues that impact these groups. It highlights the complex relationships between native groups and the physical and social environments in which they live--From publisher description.